2021
DOI: 10.3897/mycokeys.85.70829
|View full text |Cite
|
Sign up to set email alerts
|

Two new asexual genera and six new asexual species in the family Microthyriaceae (Dothideomycetes, Ascomycota) from China

Abstract: The family Microthyriaceae is represented by relatively few mycelial cultures and DNA sequences; as a result, the taxonomy and classification of this group of organisms remain poorly understood. During the investigation of the diversity of aquatic hyphomycetes from southern China, several isolates were collected. These isolates were cultured and sequenced and a BLAST search of its LSU sequences against data in GenBank revealed that the closest related taxa are in the genus Microthyrium. Phylogenetic analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(107 reference statements)
0
6
0
1
Order By: Relevance
“…Tomando en cuenta que en las últimas décadas se han descrito una extraordinaria cantidad de especies de MA asociados a hojas de muy diferentes tipos de plantas (Delgado y Miller, 2017;Crous et al 2020;Qiao et al 2021), se piensa que la exploración taxonómica de las comunidades fúngicas asociadas a los restos vegetales puede aportar valiosa información al conocimiento global de la diversidad fúngica (Tennakoon et al, 2021). En particular para México, ante la gran diversidad de Quercus spp.…”
Section: Discussionunclassified
“…Tomando en cuenta que en las últimas décadas se han descrito una extraordinaria cantidad de especies de MA asociados a hojas de muy diferentes tipos de plantas (Delgado y Miller, 2017;Crous et al 2020;Qiao et al 2021), se piensa que la exploración taxonómica de las comunidades fúngicas asociadas a los restos vegetales puede aportar valiosa información al conocimiento global de la diversidad fúngica (Tennakoon et al, 2021). En particular para México, ante la gran diversidad de Quercus spp.…”
Section: Discussionunclassified
“…Hongsanan et al [ 12 ] added two new asexual genera and provided a holomorphic family description. Two new Triscelophorus species were introduced by Qiao et al [ 13 ], and the systematic placement of Triscelophorus was confirmed within Microthyriaceae. Recently, four asexual genera were introduced to the family [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two new Triscelophorus species were introduced by Qiao et al [ 13 ], and the systematic placement of Triscelophorus was confirmed within Microthyriaceae. Recently, four asexual genera were introduced to the family [ 13 , 14 ]. So far, Microthyriaceae contains 16 genera, including eight asexual genera, Antidactylaria , Hamatispora , Isthmomyces , Keqinzhangia , Neoanungitea , Pseudocoronospora , Pseudopenidiella , and Triscelophorus [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations